An Antiaging Electrolyte Additive for High‐Energy‐Density Lithium‐Ion Batteries. Issue 20 (6th April 2020) - Han, Jung‐Gu; Hwang, Chihyun; Kim, Su Hwan; Park, Chanhyun; Kim, Jonghak; Jung, Gwan Yeong; Baek, Kyungeun; Chae, Sujong; Kang, Seok Ju; Cho, Jaephil; Kwak, Sang Kyu; Song, Hyun‐Kon; et al.
Abstract: High‐capacity Li‐rich layered oxide cathodes along with Si‐incorporated graphite anodes have high reversible capacity, outperforming the electrode materials used in existing commercial products. Hence, they are potential candidates for the development of high‐energy‐density lithium‐ion batteries (LIBs). However, structural degradation induced by loss of interfacial stability is a roadblock to their practical use. Here, the use of malonic acid‐decorated fullerene (MA‐C60 ) with superoxide dismutase activity and water scavenging capability as an electrolyte additive to overcome the structural instability of high‐capacity electrodes that hampers the battery quality is reported. Deactivation of PF5 by water scavenging leads to the long‐term stability of the interfacial structures of electrodes. Moreover, an MA‐C60 ‐added electrolyte deactivates the reactive oxygen species and constructs an electrochemically robust cathode‐electrolyte interface for Li‐rich cathodes. This work paves the way for new possibilities in the design of electrolyte additives by eliminating undesirable reactive substances and tuning the interfacial structures of high‐capacity electrodes in LIBs. Abstract : A malonic acid‐decorated fullerene (MA‐C60 ) with superoxide dismutase activity and water scavenging capability is used as an effective electrolyte additive to enhance the interfacial stability of high‐capacity electrodes.